PENGARUH VARIASI PUPUK TERHADAP LAJU PERTUMBUHAN MIKROALGA DIATOM Chaetoceros calcitrans - Azkiya, Azmi Binta; Indriyawati, Novi; Wulandari, Destin Retno; Amanda, Vevilia Tri; Supriyanto, Supriyanto (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2025)
The use of Pro Analis fertilizer with uneconomical prices in microalgae culture has been a problem that has hampered the utilization of microalgae. The use of agricultural fertilizers as a more economical source of nutrients. This study was conducted to determine the density value of microalgae cultured using agricultural fertilizers to determine which agricultural fertilizers support the cultivation of Chaetoceros calcitrans. This study was conducted using an experimental method, the study was conducted on a laboratory scale with 4 treatments with a research design P1 using variations of Urea Silica fertilizer; P2 NPK and silica; and P3 Urea, NPK and Silica with a ratio of Urea; NPK; Silica fertilizer (0.1; 0.1; 0.015 gr / L). The results of data analysis show that the provision of fertilizer variation treatment has a significant difference (≤0.05) and has a positive correlation with a very strong correlation (r = 0.656) and R2 = 0.431 which shows that the provision of fertilizer variation affects the density value of the Chaetoceros calcitrans microalgae by 43.1% with the provision of NPK and silica fertilizer variation treatment (P2) resulting in the highest density of 291 x104 and the largest cell size with a size of 3.566 µm with these results indicating the ability of agricultural fertilizers as a substitute source of nutrients in microalgae culture.